2019
DOI: 10.1177/0300060519826449
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of urethroplasties to reduce urethral strictures in patients with severe hypospadias

Abstract: Objective Transverse island pedicle flap (TIPF) plus transected urethral plate-preserving urethroplasty is increasingly used for treatment of severe hypospadias. We aimed to reduce the occurrence of urethral strictures in patients undergoing such procedures. Methods Sixty-five patients with severe hypospadias were enrolled. Thirty-two patients underwent onlay-tube-onlay urethroplasty (Group A), and 33 patients underwent modified Duplay urethroplasty (Group B). Postoperative complications were recorded, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Our previous study reported on the application of onlaytube-onlay in treating severe hypospadias with obvious chordee. Using the advantages of both Duckett and Onlay, this technique used the dorsal TPIF and the transected urethral plate to form a new urethra (9,10). According to our previous study, only 9.3% developed urethral stricture among the 32 pediatric patients who received one-stage repair for severe hypospadias, which was significantly lower than that of Duckett (11).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported on the application of onlaytube-onlay in treating severe hypospadias with obvious chordee. Using the advantages of both Duckett and Onlay, this technique used the dorsal TPIF and the transected urethral plate to form a new urethra (9,10). According to our previous study, only 9.3% developed urethral stricture among the 32 pediatric patients who received one-stage repair for severe hypospadias, which was significantly lower than that of Duckett (11).…”
Section: Discussionmentioning
confidence: 99%
“…Sub coronal or distal hypospadias is associated with the opening of the meatus near the proximity of the glans, midshaft hypospadias is referred to as the opening of the meatus anywhere along the shaft of the penis, and proximal or penoscrotal hypospadias is characterized by the opening of urethral meatus at the junction of penis and scrotum [2]. Hypospadias is a congenital condition and is considered one of the most common congenital defects of males with epidemiological studies showing a prevalence of 1 in 200 births [3]. The aetiology of hypospadias is currently not well defined however recent establishment in the study shows that the aetiology of hypospadias is multifactorial with complex correlations between environmental factors, endocrine pathologies, and genetic influence [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, this classification does not provide effective guidance for selecting clinical treatments 4,5 . Severe hypospadias is, in most cases, accompanied by apparent penile curvature and severe clinical symptoms, which require more involved surgical reconstruction, whereas mild cases do not always require surgical repair 4–7 …”
mentioning
confidence: 99%
“…4,5 Severe hypospadias is, in most cases, accompanied by apparent penile curvature and severe clinical symptoms, which require more involved surgical reconstruction, whereas mild cases do not always require surgical repair. [4][5][6][7] As hypospadias is often associated with multiple syndromes and additional genitourinary abnormalities, the diagnosis of prenatal hypospadias, especially severe hypospadias, may be of high value to the clinical team and parents as it allows early counseling and directs further testing. [8][9][10] Currently, prenatal diagnosis of hypospadias relies mainly on ultrasound (US).…”
mentioning
confidence: 99%